2021
DOI: 10.3389/fped.2021.673957
|View full text |Cite
|
Sign up to set email alerts
|

Immune Dysregulation Mimicking Systemic Lupus Erythematosus in a Patient With Lysinuric Protein Intolerance: Case Report and Review of the Literature

Abstract: Lysinuric protein intolerance (LPI) is an inborn error of metabolism caused by defective transport of cationic amino acids in epithelial cells of intestines, kidneys and other tissues as well as non-epithelial cells including macrophages. LPI is caused by biallelic, pathogenic variants in SLC7A7. The clinical phenotype of LPI includes failure to thrive and multi-system disease including hematologic, neurologic, pulmonary and renal manifestations. Individual presentations are extremely variable, often leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
0
12
0
1
Order By: Relevance
“…A significant number of genes associated with autoinflammation and autoimmunity have been implicated in monogenic lupus, including SLC7A7 [ 4 6 ]. The compound heterozygous variants in SLC7A7 , namely, c.475C > T (p. Arg159Cys) and c.1001 T > G (p. Leu334Arg), were detected in a patient who clinically presented with immune dysregulation in the setting of early onset SLE [ 28 ]. Li et al [ 27 ] reported five mutations of SLC7A7 : c.625+1G > A, c.235G > A, c.1085 T > C, c.1387delG, and c.1215G > A, which were identified as causative mutations of SLE in 4 of 52 Chinese pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of genes associated with autoinflammation and autoimmunity have been implicated in monogenic lupus, including SLC7A7 [ 4 6 ]. The compound heterozygous variants in SLC7A7 , namely, c.475C > T (p. Arg159Cys) and c.1001 T > G (p. Leu334Arg), were detected in a patient who clinically presented with immune dysregulation in the setting of early onset SLE [ 28 ]. Li et al [ 27 ] reported five mutations of SLC7A7 : c.625+1G > A, c.235G > A, c.1085 T > C, c.1387delG, and c.1215G > A, which were identified as causative mutations of SLE in 4 of 52 Chinese pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene causes LPI, a rare recessive disorder characterized by FTT, growth retardation, muscle hypotonia and hepatosplenomegaly [ 45 ]. Mostly appeared after weaning of breastmilk, clinical manifestations of LPI can be widely variable resembling the findings in urea cycle disorders such as hyperammonemia [ 46 ]. Overlapping manifestation of LPI and SLE has been reported in several case series [ 11 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly appeared after weaning of breastmilk, clinical manifestations of LPI can be widely variable resembling the findings in urea cycle disorders such as hyperammonemia [ 46 ]. Overlapping manifestation of LPI and SLE has been reported in several case series [ 11 , 46 ]. Renal involvement is a frequent and progressive complication in LPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMGs provided educational and networking opportunities by hosting in-person courses attended by over 300 analysts and researchers, including the Mendelian Data Analysis Workshop (University of Washington), Interpreting Genomes for Rare Disease (Broad), and McKusick Short Course in Human and Mammalian Genetics (Baylor-Hopkins). The CMGs have enabled researchers and clinicians investigating rare Mendelian diseases around the world to access gene discovery techniques, including those in countries where access to research opportunities is limited, such as the Democratic Republic of the Congo, 27 South Africa, Kenya, Egypt, 28,29 Iraq, 30 Chile, 31,32 Turkey, [33][34][35] and Lithuania. For some, this has involved training opportunities within a CMG-affiliated laboratory, whereas for others, learning happened through collaborative meetings to discuss analysis results on teleconferences.…”
Section: Impact On the Rare Disease Communitymentioning
confidence: 99%